13.1k views
1 vote
If s(x)=x-7 and t(x)=4x^2-x+3 which expression is equivalent to (txs)(x)?

User Anisia
by
5.6k points

1 Answer

4 votes

For this case we have by definition that:


(f * g) (x) = f (x) * g (x)

In this case we must find
(t * s) (x), so:

(
(t * s) (x) = t (x) * s (x) = (4x ^ 2-x + 3) * (x-7) =

We must apply distributive property that states that:


(a + b) (c + d) = ac + ad + bc + bd

So:


(4x ^ 2-x + 3) * (x-7) = 4x ^ 3-28x ^ 2-x ^ 2 + 7x + 3x-21 = 4x ^ 3-29x ^ 2 + 10x-21

Answer:


4x^3-29x^2+10x-21

User Afiefh
by
5.2k points